2013
DOI: 10.1038/ncomms3294
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and bright organic light-emitting diodes on single-layer graphene electrodes

Abstract: Organic light-emitting diodes are emerging as leading technologies for both high quality display and lighting. However, the transparent conductive electrode used in the current organic light-emitting diode technologies increases the overall cost and has limited bendability for future flexible applications. Here we use single-layer graphene as an alternative flexible transparent conductor, yielding white organic light-emitting diodes with brightness and efficiency sufficient for general lighting. The performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
200
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(205 citation statements)
references
References 56 publications
5
200
0
Order By: Relevance
“…[35,162] However, only a few groups have demonstrated the use of a single layer of graphene as the anode in small-area OLED devices. [163] …”
Section: Transparent Electrodes As Front Electrodes In Oledsmentioning
confidence: 99%
“…[35,162] However, only a few groups have demonstrated the use of a single layer of graphene as the anode in small-area OLED devices. [163] …”
Section: Transparent Electrodes As Front Electrodes In Oledsmentioning
confidence: 99%
“…1,2 The use of graphene as a potential replacement of brittle and increasingly expensive indium tin oxide (ITO) as a transparent conducting electrode (TCE) in organic electronics and optoelectronic applications has attracted a lot of research interest, [3][4][5][6] but effective integration into working devices remains challenging.…”
mentioning
confidence: 99%
“…This requirement can be satised by introducing dopant during the transfer process, and this has been broadly studied. 20,41,42 During the above studies, it was found that the pH value decreases as the etching process proceeds. Thus, H + ions as dopant were systemically studied herein to determine if this could further improve graphene lms.…”
Section: Resultsmentioning
confidence: 99%